An Authentic Project-Based Assessment Model for Vocational High School Students Grade X - Anastasia Sastrikirana (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2015)
The aim of Indonesia National Education is to bring its people and country towards better development of skills and characters or attitude in order to be democratic and responsible citizens. A curriculum needs to be created in order to support the achievement of this goal. The current curriculum 2013, has tried to emphasize on knowledge, skills and attitude all of which are in line with the goal of Indonesia National Education. It emphasizes on three types of learning namely project-based, problem-based, and discovery learning in order to promote more skilful people. Yet, it is problematic in some ways for it does not provide enough time allocation for knowledge and skill development. English is now taught in one meeting only in a week. Also, the problem lies in the assessment. It separates the assessment of knowledge, skills, and attitude. It seems to forget that in those types of learning, students have to integrate those aspects in order to accomplish a projector to solve a problem. The partial assessment makes those types of learning impossible. Therefore, an alternative authentic and holistic assessment for a year project for vocational high school students is developed to improve students‟ progress as a whole.